Strategi Digital Marketing Dan Selebgaram Batam Sebagai Sarana Mengembangkan UMKM Afo Cake & Catering - Renny Christiarini Christiarini; Yohana Juwitasari Hulu (ConCEPt - Conference on Community Engagement Project, 2023)
The practical work carried out aims to provide solutions to the problems faced by Partners. In developing a business and increasing sales, it is necessary to use digital marketing to increase sales, this technique has been carried out by many entrepreneurs. The author collects data to design a marketing strategy that will be carried out by observing and interviewing business owners. The promotion method used in this study is advertising, promotion through Instagram and using celebgrams in Batam City as a medium for business promotion.